Karoo Thrush and frogs: potential food source or opportunistic attack? - Weiss, Joshua (Biodiversity Observations, 2014)
This episode may have been an attack based on curiosity, possibly because of the "unrecognisable" movement of the frog ? but it could just as well have been an attempt to prey on the frog.